1999
DOI: 10.1136/oem.56.9.625
|View full text |Cite
|
Sign up to set email alerts
|

Study of cancer incidence among 8530 male workers in eight Norwegian plants producing ferrosilicon and silicon metal.

Abstract: Objectives-To examine the association between cancer incidence, in particular incidence of lung cancer, and duration of work among employees in eight Norwegian plants producing ferrosilicon and silicon metal. Results-A total of 832 cases of cancer were observed against 786 expected (standardised incidence ratio (SIR) 1.06). Among the furnace workers an increased incidence of lung cancer (SIR 1.57) and testicular cancer (SIR 2.30) was found. Internal comparisons of rates by Poisson regression analysis among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 30 publications
0
24
1
Order By: Relevance
“…After the first 5 yr of active service, while the cancer incidence was numerically lower among the furnace workers, a marked decrease in nonfurnace workers was noted for the person-years of all remaining periods of active employment (SIR 0.24; 95% CI 0.07-0.61). This result was not explained by Hobbesland et al (1999), who concluded that the study had not identified any causal factors and that the role of Mn remained unclear. Kjuus et al (1986) investigated total mortality and cancer incidence during et al 1996) Cohort study investigating mortality of glassworkers exposed to Mn and other metals in 11 parishes in a glass-producing area of Sweden.…”
Section: Carcinogenicitycontrasting
confidence: 67%
See 3 more Smart Citations
“…After the first 5 yr of active service, while the cancer incidence was numerically lower among the furnace workers, a marked decrease in nonfurnace workers was noted for the person-years of all remaining periods of active employment (SIR 0.24; 95% CI 0.07-0.61). This result was not explained by Hobbesland et al (1999), who concluded that the study had not identified any causal factors and that the role of Mn remained unclear. Kjuus et al (1986) investigated total mortality and cancer incidence during et al 1996) Cohort study investigating mortality of glassworkers exposed to Mn and other metals in 11 parishes in a glass-producing area of Sweden.…”
Section: Carcinogenicitycontrasting
confidence: 67%
“…In a further cohort study by Hobbesland et al (1999) on the same population, associations between cancer incidence and duration of work were investigated. The cohort consisted of 6363 men first employed during 1933-1991 for at least 6 mo.…”
Section: Carcinogenicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al [1995] have found an increased risk (OR 1.7, 95% CI 1.1-2.6) for testicular cancer among workers exposed to extreme temperatures, i.e., exceeding 808F (278C) or less than 608F (168C). A study of ferrosilicon workers exposed to high temperatures showed an increased risk for testicular cancer, which was not observed among other workers in the same plant [Hobbesland et al, 1999]. However, the hypothesis of an increased risk due to elevated temperature has not been supported by other studies [Karagas et al, 1989;UK Testicular Cancer Study Group, 1994].…”
Section: Discussionmentioning
confidence: 95%